Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1105/tpc.110.081489
|View full text |Cite
|
Sign up to set email alerts
|

12-Oxo-Phytodienoic Acid Accumulation during Seed Development Represses Seed Germination inArabidopsis     

Abstract: Arabidopsis thaliana COMATOSE (CTS) encodes an ABC transporter involved in peroxisomal import of substrates for b-oxidation. Various cts alleles and mutants disrupted in steps of peroxisomal b-oxidation have previously been reported to exhibit a severe block on seed germination. Oxylipin analysis on cts, acyl CoA oxidase1 acyl CoA oxidase2 (acx1 acx2), and keto acyl thiolase2 dry seeds revealed that they contain elevated levels of 12-oxo-phytodienoic acid (OPDA), jasmonic acid (JA), and JA-Ile. Oxylipin and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 80 publications
8
195
1
Order By: Relevance
“…A combination of genetics and feeding experiments has demonstrated that 12-OPDA interacts with ABA, inhibits seed germination, and increases ABA INSENSITIVE5 protein (Dave et al, 2011;Dave and Graham, 2012). These results, collectively, further highlight the importance of fine-tuning of jasmonate signatures in response to environmental and developmental signals and signify the stimulusdependent balance in levels of plant hormones and, by extension, their interactions.…”
Section: Discussionmentioning
confidence: 76%
“…A combination of genetics and feeding experiments has demonstrated that 12-OPDA interacts with ABA, inhibits seed germination, and increases ABA INSENSITIVE5 protein (Dave et al, 2011;Dave and Graham, 2012). These results, collectively, further highlight the importance of fine-tuning of jasmonate signatures in response to environmental and developmental signals and signify the stimulusdependent balance in levels of plant hormones and, by extension, their interactions.…”
Section: Discussionmentioning
confidence: 76%
“…These results suggest that to promote dormancy, MFT acts downstream with or parallel to the ABA and GA response pathways. We reported recently that the pxa1 mutant (that is disrupted in a peroxisomal ABC transporter activity) has low levels of seed germination despite accumulating higher GA levels than WT (45). Hence, the high ABA and GA levels in mft and pxa1 mutants, respectively, may be a consequence of compensatory mechanisms attempting to rescue germination back to WT levels.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrazolium staining of Arabidopsis seeds has been described (23) and took place in the dark at 30°C for 48 h. PA analysis was performed as described (39,40) using freshly harvested flash frozen seeds. LC-MS analysis of phytohormones and phenylpropanoids has been described previously (24,41). Significance was tested using the T statistic.…”
Section: Methodsmentioning
confidence: 99%